Acoustic perception and emotion evocation by rock art soundscapes of Altai (Russia) - Samantha López-Mochales; Samantha López-Mochales; Raquel Aparicio-Terrés; Raquel Aparicio-Terrés; Margarita Díaz-Andreu; Margarita Díaz-Andreu; Margarita Díaz-Andreu; Carles Escera; Carles Escera; Carles Escera; Carles Escera (Frontiers in Psychology, 2023)
The major goal of psychoarchaeoacoustics is to understand the psychology behind motivations and emotions of past communities when selecting certain acoustic environments to set activities involving the production of paintings and carvings. Within this framework, the present study seeks to explore whether a group of archaeological rock art sites in Altai (Siberia, Russia) are distinguished by particular acoustic imprints that elicit distinct reactions on listeners, in perceptual and emotional terms. Sixty participants were presented with a series of natural sounds convolved with six impulse responses from Altai, three of them recorded in locations in front of rock art panels and three of them in front of similar locations but without any trace of rock art. Participants were interrogated about their subjective perception of the sounds presented, using 10 psychoacoustic and emotional scales. The mixed ANOVA analyses carried out revealed that feelings of “presence,” “closeness,” and “tension” evoked by all sounds were significantly influenced by the location. These effects were attributed to the differences in reverberation between the locations with and without rock art. Despite results are not consistent across all the studied rock art sites, and acknowledging the presence of several limitations, this study highlights the significance of its methodology. It stresses the crucial aspect of incorporating the limitations encountered in shaping future research endeavors.